Notes for media reinvention - Flores-Vivar, Jesús Miguel (2009)
Journalism and media are going through a change of era. This change is reflected in the transformation of journalism and media-lived and that another major in 1980 that became known as mediamorphosis, by this, professionals have to learn new roles. The impact of information technology and Internet has changed the way how you present the news and, most importantly, transform the business model that has characterized media companies. This article analyzes the current situation provides some strategic guidelines to be followed by some media-and-do and studied some of the new profiles arebeginning to emerge as a result of the reinvention of journalism and the media.